Strategi Guru dalam Mengelola Emosi (Emotional Intelligence) dalam menghadapi Siswa Aktif di Kelas - Fahira Intan Ukhrowi; Ikrimatul Uyun; Ilman Derajat; Mu’allimin Mu’allimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This research is based on the reality that classroom management often tests teachers' emotional stability, especially when dealing with highly active students. This study focuses on how teachers use emotional intelligence to control themselves when facing challenging learning situations. The purpose of this study is to describe the forms of emotional regulation carried out by teachers and their influence on the effectiveness of classroom management. The research was conducted using a qualitative descriptive approach through observations and interviews with teachers. The results show that effective emotional management is carried out through several methods, such as increasing self-awareness to recognize stress triggers, pausing before responding to student behavior, and trying to understand the background of student activity through empathy. Teachers with good emotional intelligence tend to be able to direct student activity into more positive learning participation, rather than responding to it with reactive or authoritarian responses. This study emphasizes the importance of strengthening psychological aspects and emotional management skills in teacher professional development programs. Emotional maturity not only helps create a more harmonious classroom atmosphere but also forms the basis for inclusive learning interactions and supports the continuous development of student character.